STRATEGI KEUNGGULAN BERSAING DALAM MENINGKATKAN KINERJA PEMASARAN DIMASA PANDEMI COVID-19 (Studi pada Peternakan UD.Baqoroh Joyo, Sidoarjo Jawa Timur) - Mujita Fajar Nataraningtyas; Lisa Sulistyawati (Universitas Halu Oleo, 2022)
This research was conducted with the aim of knowing and analyzing competitive advantage strategies in improving marketing performance implemented by UD. Baqoroh Joyo during the covid-19 pandemic, to find out and analyze marketing performance during the covid-19 pandemic. The research method used is descriptive qualitative method with SWOT analysis method and data collection techniques through deep interviews, surveys, observations, questionnaires, and documentation in identifying strengths, weaknesses, opportunities, and threats at UD. Baqoroh Joyo. Based on the calculation of the results of IFAS EFAS shows that UD. Baqoroh Joyo has IFAS results with a strength score of 2.87 and a weakness score of 0.28, while the EFAS results show an opportunity score of 2.63 and a threat score of 0.43. Based on the diagram, the results of the SWOT analysis show that UD. Baqoroh Joyo is in Quadrant I with a SO (Strength Opportunity) strategy. In this situation it means UD. Baqoroh Joyo The company must maximize and use its strengths and opportunities to strengthen its position. So that the strategy that can be applied can support an aggressive growth policy (growth-oriented strategy) in improving marketing performance during the COVID-19 pandemic.